2007
DOI: 10.1897/07-515
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Progesterone in Loblolly Pine: A Major Steroid Precursor of Environmental Androgens

Abstract: Progesterone, androstenedione, and androstadienedione were previously identified in the water and sediment of the Fenholloway River (Taylor County, FL, USA), a river that contains populations of masculinized female mosquitofish downstream of a paper mill, at levels higher than those in the nearby Spring Creek. Plant sterols, such as beta-sitosterol in mill effluent derived from pine tree pulp, were suggested to be metabolized by bacteria to progesterone and androgens to account for the masculinization phenomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Although only little information is available regarding the endocrine effects of hydroxylated ADDs and ADs, they might also have androgenic potential, since exogenous steroids with similar structures to testosterone affect the androgen signaling pathways in vertebrates [ 164 , 165 ]. Similarly, endocrine effects of bacterial sterol degradation on fish were suggested: masculinization of fish populations in rivers receiving paper-mill effluents [ 166 , 167 , 168 ] was traced back to the bacterial transformation of plant-derived sterols into androgenic steroids [ 169 , 170 , 171 ].…”
Section: Potential Ecological Effects Of Bacterial Bile-acid Degradationmentioning
confidence: 99%
“…Although only little information is available regarding the endocrine effects of hydroxylated ADDs and ADs, they might also have androgenic potential, since exogenous steroids with similar structures to testosterone affect the androgen signaling pathways in vertebrates [ 164 , 165 ]. Similarly, endocrine effects of bacterial sterol degradation on fish were suggested: masculinization of fish populations in rivers receiving paper-mill effluents [ 166 , 167 , 168 ] was traced back to the bacterial transformation of plant-derived sterols into androgenic steroids [ 169 , 170 , 171 ].…”
Section: Potential Ecological Effects Of Bacterial Bile-acid Degradationmentioning
confidence: 99%
“…The source of these progesterones is most likely the loblolly pine ( Pinus taeda L. ) which is highly prevalent along this entire area [38]. As anal fin elongation is found only at the Fenholloway River, this suggests that the causative chemical is specific to that site or may be related to a combined effect from both progesterone and androgen loads.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of low levels of AR-active chemicals at both sites may be due to the breakdown of this chemical from high levels of progesterones in the sediments via microorganisms [37] . The source of these progesterones is most likely the loblolly pine ( Pinus taeda L. ) which is highly prevalent along this entire area [38] . As anal fin elongation is found only at the Fenholloway River, this suggests that the causative chemical is specific to that site or may be related to a combined effect from both progesterone and androgen loads.…”
Section: Discussionmentioning
confidence: 99%
“…In 1964, Leboeuf, Cavé, and Goutarel reported that progesterone was found in Holarrhena floribunda leaves [1]. Since then progesterone and its congeners were successively reported to be present in apple seeds [2], loblolly pine [3], common foxglove ( Digitalis purpurea L.), tobacco ( Nicotiana tabacum L.), elecampane ( Inula helenium L.) [4], Juglans regia [5] , Adonis aleppica [5], and wheat [6], mostly using chromatographic methods, but also via isolation [5]. Other mammalian steroid hormones have been reported in plants.…”
Section: Introductionmentioning
confidence: 99%